Recurrence after resection with curative intent for distal cholangiocarcinoma. Issue 4 (31st January 2017) - Komaya, K; Ebata, T; Shirai, K; Ohira, S; Morofuji, N; Akutagawa, A; Yamaguchi, R; Nagino, M; Aoba, T; Kaneoka, Y; Arai, T; Shimizu, Y; et al.
Abstract: Background: Few studies have been conducted on patterns of recurrence after resection for distal cholangiocarcinoma (DCC). The aim of this study was to investigate the incidence and pattern of recurrence after resection of DCC, and to evaluate prognostic factors for time to recurrence and recurrence-free survival (RFS). Methods: Patients who underwent pancreatoduodenectomy with curative intent for DCC between 2001 and 2010 at one of 30 hospitals in Japan were reviewed retrospectively, with special attention to recurrence patterns. The Cox proportional hazards model was used for multivariable analysis. Results: In the study interval, 389 patients underwent pancreatoduodenectomy for DCC with R0/M0 status. Recurrence developed in 213 patients (54·8 per cent). The estimated cumulative probability of recurrence was 54·3 per cent at 5 years. An initial locoregional recurrence occurred in 55 patients (14·1 per cent) and initial distant recurrence in 168 (43·2 per cent), most commonly in the liver. Isolated initial locoregional recurrence occurred in 45 patients (11·6 per cent). Independent prognostic factors for time to recurrence and RFS were perineural invasion ( P = 0·001 and P = 0·009 respectively), pancreatic invasion (both P < 0·001) and lymph node metastasis (both P < 0·001). RFS worsened as the number of risk factors increased: the 5-year RFS rate was 70·6 per cent for patients without any risk factors, 50·3 per cent for patients with one factor, 31·8 per cent for those with two factors, and 13·4 per cent when three factors were present. Conclusion: More than half of patients with DCC experienced recurrence after R0 resection, usually within 5 years. Perineural invasion, pancreatic invasion and positive nodal involvement are risk factors for recurrence. Abstract : Adjuvant therapy warranted in selected patients